Risk Marker or Risk Mechanism? The Effect of Family, Household, and Parental Imprisonment on Children and Adults’ Social Support and Mental Health - Besemer, Kirsten L. (Criminal justice and behavior, 2018)
There is robust evidence of associations between parental imprisonment (PI) and a variety of harms to children, but the consequences of other forms of family imprisonment are largely unknown. Using Household, Income, and Labour Dynamics in Australia (HILDA), a nationally representative Australian data set, this article looked at the direct effects of PI, household member imprisonment (HI), or close family member imprisonment (CFI) on the social support and mental health of nonincarcerated adults and young people. Recent PI, HI, or CFI had no association with social support. Recent CFI did increase men’s risk of poor mental health, but not women’s or young people’s. We consider the implications of these findings in the context of strong negative effects of paternal imprisonment on mothers in the United States.